FAKTOR KEBERHASILAN UTAMA PADA PEKERJAAN PROYEK KONSTRUKSI JALAN DI PROVINSI SUMATERA BARAT - Fisher, Mart; Utama, Lusi; Anif, Bahrul (Rang Teknik Journal, 2025)
The success of a project is the primary goal for companies engaged in construction services. The aim of this study is to identify the factors influencing the main success of contractors in road construction projects in West Sumatra Province and to propose solutions for improving contractor performance in future construction projects using the POAC method. This study employs a quantitative approach, utilizing questionnaires to collect data. The research results reveal six key factors affecting the primary success of contractors in road construction projects in West Sumatra Province: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy, and Workforce factors.Keywords: Success, Project, Factors, POAC